2019
DOI: 10.1007/s00018-019-03330-y
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A6 modulates TBC1D15/Rab7/StARD3 axis to control endosomal cholesterol export in NPC1 cells

Abstract: Cholesterol accumulation in late endosomes is a prevailing phenotype of Niemann-Pick type C1 (NPC1) mutant cells. Likewise, annexin A6 (AnxA6) overexpression induces a phenotype reminiscent of NPC1 mutant cells. Here, we demonstrate that this cellular cholesterol imbalance is due to AnxA6 promoting Rab7 inactivation via TBC1D15, a Rab7-GAP. In NPC1 mutant cells, AnxA6 depletion and eventual Rab7 activation was associated with peripheral distribution and increased mobility of late endosomes. This was accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 99 publications
(166 reference statements)
6
78
0
Order By: Relevance
“…L. Liscum (Tufts University School of Medicine, Boston, MA, USA) and D. Ory (Washington University, St. Louis, MO, USA). The AnxA6-depleted CHO M12-A6ko cell line was generated in our laboratories using CRISPR/Cas9 editing technology as described [25]. Control (GM5659D) and NPC1 mutant human skin fibroblasts (GM03123) were from the Coriell Institute for Medical Research (Camden, NJ, USA) and cultured in DMEM, 10% FCS, L-glutamine (2 mM), penicillin (100 units/mL), and streptomycin (100 µg/mL) at 37 • C, 5% CO 2 .…”
Section: Cells Reagents Cell Culture and Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…L. Liscum (Tufts University School of Medicine, Boston, MA, USA) and D. Ory (Washington University, St. Louis, MO, USA). The AnxA6-depleted CHO M12-A6ko cell line was generated in our laboratories using CRISPR/Cas9 editing technology as described [25]. Control (GM5659D) and NPC1 mutant human skin fibroblasts (GM03123) were from the Coriell Institute for Medical Research (Camden, NJ, USA) and cultured in DMEM, 10% FCS, L-glutamine (2 mM), penicillin (100 units/mL), and streptomycin (100 µg/mL) at 37 • C, 5% CO 2 .…”
Section: Cells Reagents Cell Culture and Transfectionsmentioning
confidence: 99%
“…AnxA6-dependent Rab7 inactivation in NPC1 mutant cells was associated with a reduction of MCS between LE/Lys and the ER. Vice versa, AnxA6 depletion in NPC1 mutant cells caused elevated Rab7 activity, increased MCS formation, and significantly reduced the amount of cholesterol in LE/Lys [25].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, NPC1 meets all the criteria for a tether and appears to be an important regulator of MCS formation. Reduced MCS on loss of NPC1 activity was also found to be associated with reduced GTP‐bound (active) Rab7 due to recruitment of the Rab7 GAP TBC1D15 by endosomal AnnexinA6 . GTP‐Rab7 was restored on depletion of AnnexinA6, resulting in increased ER‐LE/Lys MCS and, excitingly, reversal of the cholesterol accumulation.…”
Section: Role Of Mcs In Cellular Distribution Of Ldl‐derived Cholesterolmentioning
confidence: 87%
“…This explains how NPC1 transports cholesterol from the LE/Lys lumen to the cytosolic leaflet of the limiting membrane, but the next step in cholesterol egress, transport from the limiting membrane to the ER, has remained elusive. Two independent studies, one from our lab and the other from Meneses‐Salas et al, have gone some way to resolving this fundamental gap in our knowledge, uncovering an additional role for NPC1 in MCS formation . Both studies found that ER‐LE/Lys MCS were reduced on loss of functional NPC1, suggesting a regulatory role for NPC1 in MCS formation.…”
Section: Role Of Mcs In Cellular Distribution Of Ldl‐derived Cholesterolmentioning
confidence: 88%
See 1 more Smart Citation